Interventions for Supporting Career Transition among Students with Visual Impairments - Eseadi, Chiedu (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2023)
Purpose: Various interventions and career support services are necessary to aid visually impaired students in transitioning to a new career and becoming fully integrated into society. This article examined some interventions for assisting students with visual impairments (VI) to experience a smooth career transition. Design/Methods/approach: This research was conducted using a narrative-integrative review research approach. From an array of data sources, an investigator can provide a viewpoint on a subject matter by using a narrative-integrative review. Findings/Results: The interventions for assisting students with visual impairments in the career transition process were classified in this article as educational interventions, family participation interventions, work-based learning interventions, interagency and transition service intervention, career mentoring as an intervention, knowledge of career and job-searching ability as an intervention, and transition programs as intervention. The author in this article addressed various issues associated with the implementation of the interventions. Also, the author discussed strategies that can be adopted to facilitate the implementation of the interventions in order to promote the career transitioning of students with visual impairments. Implications: There is a need for collaboration in implementing interventions toward facilitating career transition for students with VI. The interventions outlined in this article should be implemented collaboratively by a team of teachers, psychologists, career professionals, families, and other important agencies. Using the article as a point of reference, it will be possible to categorize and target interventions to facilitate career transition for students with VI.